A Woman Giving First Birth with Pubic Symphysis Rupture: A Case Report - Rusnaidi; Muhammad Budiman (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Physical changes during pregnancy cause stretching of the pubic symphysis. Pubic symphysis rupture occurs when the joint widening is more than 10 mm which is confirmed by radiologic. The conservative and surgical are required to management of rupture of the symphysis. 25-year-old women with a postpartum birth canal tear using a vacuum. The patient felt severe pain and a lump in the pubic area. On examination, the uterus was 2 fingers below the navel, swelling in symphysis area, and pressure pain, and there were the labia and urethra lacerated without active bleeding. in laboratory tests, hemoglobin 7.3 g/dL, leukocytes 15,300/mm3, and platelets 255,000/mm3. The results of the pelvic x-ray examination are symphisiolysis. The patient underwent surgery with open reduction internal fixation (ORIF) and suturing the lacerated urethra by the surgical department. During the treatment, light mobilization and education on self and baby care were carried out. The wound was cleaned in 3 days and the urinary catheter was maintained for up to 14 days. The patient was discharged and carried out control every month for 6 months. Pubic symphysis rupture is one of the rare complications of labor due to multiparity, macrosomia, use of forceps, difficult labor, malpresentation, and trauma. The diagnosis is made when the intrapubic distance is greater than 10 mm on pelvic radiography. An MRI examination is preferred to assess for tissue tears. Operative internal fixation is performed when conservative therapy fails, soft tissue damage, and intrapubic distance of more than 25 mm. Pubic symphysis rupture is a labor complication due to the stretching of the symphysis. Surgical treatment is performed when conservative therapy fails.